APLIKASI METODE L-MOMENT UNTUK ANALISIS BANJIR REGIONAL DI WILAYAH SUNGAI BATANGHARI PROVINSI JAMBI - , Siti Umi Kalsum,ST ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Information on flood magnitudes and their frequencies are needed for design of hydraulic structures. Regional flood frequency analysis solve the problem of estimating the extreme flood events in Batanghari River Basin for catchments having short data records or ungauged catchments,such as L-moment method which are linear combination of order statistics. The main advantage of Lmoments over conventional moments is that they suffer less from the effect of sampling variability. It is more robust to outliers and virtually unbiased for small samples. L-Moment method is applied at 18 selected watershed of Batanghari River in Jambi Province and outlier tests. The regional flood frequency analysis using L-moments consists of four steps (1) screening the data using the discordancy measure Di,(2) homogeneity testing using the heterogeneity measure H